Dannelse – skitse til en rekonstrueret dannelsesfilosofi - Johannes Adamsen (Tidsskrift for Professionsstudier, 2024)
The concept of character formation (Danish: dannelse; German: Bildung) is contested. This paper firstly outlines (quite briefly) a theory of ’dannelse’, dannelse as humanity/being humane, by introducing the ideal of impartiality. This implies that the concept of ’dannelse’ is derived from the philosophy of culture/philosophical anthropology, and then moved into pedagogical philosophy, thereby shifting position from something to be achieved towards a guidance. Secondly, it will be presented why and how this is meaningful for pedagogic, education and teaching, including how it helps and guides teaching, understanding, choice, and defense of subject matters. This includes, thirdly, presenting in which way thinking along a notion of ’dannelse’ gives meaning to the concept of truth, and assists in handling the ideals of enlightenment (reason, freedom, and knowledge), without ignoring the complexity and darker sides of human being.